THE ESSENCE OF WAQF AND PERPETUATION OF BENEFITS: A CASE STUDY OF JARIYAH CHARITY BY ACEHNESE ENTREPRENEURS IN MECCA - Nurhendi, Sigit; Fatahillah, Mubarok; Ulfain, Ulfain; Fatikhaeni, Salisa (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
This research aims to examine the essence of waqf and its lasting benefits through a case study of almsgiving by Acehnese entrepreneurs in Mecca. This research aims to understand how the contribution of almsgiving by Acehnese entrepreneurs can provide sustainable benefits for society. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with Acehnese entrepreneurs who participated in the almsgiving in Mecca, as well as field observations and analysis of related documents. The interview focused on the motivation, implementation process, and impact of the almsgiving. The results of the research show that almsgiving by Acehnese entrepreneurs in Mecca has a strong essence in advancing community welfare. The main motivation of entrepreneurs is to get rewards that continue to flow and contribute positively to society. The process of implementing alms is carried out with high transparency and accountability, ensuring that the benefits can be felt by many people over a long period of time. The positive impacts found include improving public facilities, education, and social welfare in Mecca. Almsgiving by Acehnese entrepreneurs in Mecca not only fulfills spiritual aspects, but also makes a real contribution to lasting social benefits. This alms model can be an example for other philanthropists in creating a sustainable impact through charity.